Maths Anxiety in College Students across Majors: A Cross-Cultural Study - Ahmed M. Helal; Eid Hamza (Educational Futures, 2013)
This study used survey data collected from two countries, Egypt and The United States of America (USA). There were 330 participants (162 males and 168 females), all of whom were undergraduate students. 169 participants were studying at Tanta University, Egypt, and 161 participants at the University of Arkansas, USA. The study aimed to investigate maths anxiety in undergraduates with different main subjects of study and across cultures. A 4×2 ANOVA was conducted to evaluate the effects of the student’s country and main subject of study (major) on maths anxiety. The results of the 4×2 ANOVA indicated a significant main effect for country, a non-significant effect for major, and a non-significant interaction effect between country and major. Furthermore, the study used a two-way ANOVA between two factors (gender and country and maths anxiety). The analysis revealed a significant main effect for country, a significant effect for gender, and a non-significant interaction effect between country and gender.